The Effectiveness Of Self-Management Techiques In Group Counseling Services To Reduce High School Students’ Off-Task - Nurria Ayu Devi Purnama; Dimas Ardika Miftah Farid (Universitas Negeri Surabaya, 2026)
Off-task is still often found in schools and becomes a challenge in classroom learning, especially at the high school level, off-task behavior can cause harm to oneself and others and can reduce academic achievement and motivation of students, some forms of off-task behavior are often joking with friends during lessons, eating in class during lessons, playing with cell phones during lessons and so on. The purpose of this study is to determine the effectiveness of group counseling with Self-management techniques in reducing students' off-task. This study uses a quantitative method using a one-group pre-test and post-test experimental design. The population in this study used 155 students at SMA Hang Tuah 1 Surabaya. The sample used in this study was 6 students consisting of 4 boys and 2 girls who were taken using a purposive random sampling technique based on high off-task criteria. From the results obtained from the Wilcoxon test on the pre-test and post-test, the data showed a significant decrease in value between the pre-test and post-test scores with an Asymp value. Sig (2-tailed) of 0.027 <0.05 indicates that the hypothesis is accepted. Therefore, it can be concluded that group counseling with self-management techniques is effective in reducing students' off-task behavior.